An artificial LAMA2-GelMA hydrogel microenvironment for the development of pancreatic endocrine progenitors. (December 2022) - Huang, Yan; Xu, Yang; Zhu, Jiachen; Wan, Jian; Xiong, Yicheng; Jiang, Zhaoyan; Zhu, Shajun; Guo, Qingsong; Li, Yuxi; Lu, Yuhua; Yu, Bin; Guo, Yibing; et al.
Abstract: The biomimetic pancreatic microenvironment improves the differentiation efficiency and function of human embryonic stem cell-derived β-cells ( S C-β cells). Thus, a laminin subunit alpha 2-gelatin methacrylate (LAMA2-GelMA) hybrid hydrogel as a bionics carrier for the formation and maturation of endocrine lineage was developed in our research, based on pancreas proteomics analysis of postnatal mice. Pancreatic endocrine cells cultured on the hybrid hydrogel in vitro, which was composed of 0.5 μg/mL LAMA2 protein and 4% GelMA, the expression of transcription factors (TFs), including NKX6.1, NKX6.2, and NEUROD1 were upregulated. Single-cell transcriptomics was performed after LAMA2 knockdown during the early differentiation of pancreatic progenitor (PP) cells, a marked decrease in the forkhead box protein A2 (FOXA2 + )/GATA-binding factor 6 (GATA6 + ) cluster was detected. Also, we clarified that as a receptor of LAMA2, integrin subunit alpha 7 (ITGA7) participated in Integrin-AKT signaling transduction and influenced the protein levels of FOXA2 and PDX1. In vivo experiments showed that, PP cells encapsulated in the LAMA2-GelMA hydrogel exhibited higher serum C -peptide levels compared to the GelMA and Matrigel groups in nude mice and reversed hyperglycemia more quickly in STZ-induced diabetic nude mice. Taken together, our findings highlighted the feasibility of constructing a pancreas-specific microenvironment based on proteomics and tissue engineering for the treatment of diabetes.